Magnolia officinalis Bark Extract Prevents Enterocyte Death in a Colitis Mouse Model by Inhibiting ROS-Mediated Necroptosis - Kang-In Lee; Hye Jin Kim; Hyungjun Kim; Min-Soo Kim; Jung Im Kim; Ki-Sun Park (MDPI AG, 2022)
Necroptosis is a form of programmed cell death with features of necrosis and apoptosis that occurs in the intestinal epithelium of patients with inflammatory bowel disease (IBD), including ulcerative colitis and Crohn's disease. In addition, necroptosis has also been observed in enterocytes in animal models of dextran sulfate sodium (DSS)-induced colitis. Thus, the discovery of natural products for regulating necroptosis may represent an important therapeutic strategy for improving IBD. We found that Magnolia officinalis bark extract (MBE) prevented weight loss and suppressed the activation of the proinflammatory cytokine IL6 in DSS-induced colitis. Furthermore, MBE restored the length of the damaged colon and decreased the expression of necroptosis markers in mice with DSS-induced colitis. In vitro, necroptosis-induced reactive oxygen species (ROS) production was reduced by MBE, and the expression of COX2, a target protein of ROS, was simultaneously suppressed. Both magnolol and honokiol, the two major bioactive compounds in MBE, inhibited necroptosis in human primary intestinal epithelial cells and colorectal adenocarcinoma cells. Our findings highlight the effectiveness of MBE in modulating enterocyte necroptosis and suggest that MBE may be developed as a natural, disease-targeting drug for the treatment of colitis.